Development of Learning Media for the Elderly to Promote Child Health in the Community - Napalai Chaimaha; Supawadee Putthinoi; Suchitporn Lersilp (Occupational Therapy International)
The purpose of this study was to develop learning media for the elderly to promote child health. The participants consisted of 172 elderly people aged 60 years and older in a suburban village of northern Thailand. This study consisted of a survey questionnaire and focus group discussions and was divided in to two phases: (1) exploring the needs of the elderly in the knowledge of child health and (2) developing learning media, so that the elderly can learn how to promote child health and evaluate its efficiency in the trial process. Results showed that the participants mostly preferred the topic of activities of daily living (ADL) in children. The learning media contributes two major contents: (a) knowledge of child development in five types of ADL performance, brushing, eating, dressing, bathing, and toileting, and (b) methods in teaching ADL skills in children. The digital contents in the learning media were proposed to experts for professional approval. Efficiency of the learning media was evaluated after the trial, when the participants expressed their opinion, and the users perceived that the learning media was effective, motivating, easy to use, and simple in the terms used, as well as appropriate in the sequence of contents and pictures and font, size, and color of the text.